Related Factors To End Of Life Care By Nurse In Intensive Care Unit - Tahir, Rusna; Mediani, Henny Suzana; Emaliyawati, Etika; S, Iqra (Universitas Aisyah Pringsewu, 2021)
Backgorund :The mortality rate of patients who were admitted in the intensive care unit has been increased. Therefore, end of life care is needed. Goals of end of life care is to helpthe patients would die with dignity and to help the familycould receive bereavement. End of life care is related with internal and external factors.Aims :This study aims to analyze the factors that related to end of life care.Methods :Thisstudy was a quantitative research withanalytic-correlation design. The samples were 62 critical care nurse, which obtained by total sampling. This study was conducted in ICU of Kendari Hospital Southeast Sulawesi. Data collection used questionnaire thenanalyzed with bivariate throughSpearman’s Rho and multivariate through logistic regresion.Results :The implementation of end of life care in ICU of Kendari Hospitalwas optimal (74%, median = 55), which was related to several factors such as knowledge (p = 0,000), moral distress (p = 0,002), patient and family characteristics = 0.009), organizational structure and culture (p = 0,000). Knowledge was the most related factor in improving the quality of end of life care (OR = 45,542) with probality 97%.Conclusion :Optimalization of end of life care is related with the personal (internal) of the nurse factors, patient and family, and organizational structure and culture. Implication :Related factors to end of life care will enrich the thought that delivered nursing care, nurse need to align knowledge with professionalism, leaving the pressures and dilemmas due to moral stress, as well foster a deep understanding of the nature of spirituality and culture sensitivity when accompanying dying patients, grows awareness that the best preferences of critical patient care are onesbenefit the patients and familys.